IMPROVING THE REGIONAL FOOD MARKET IMPLEMENTATION MECHANISM - Abdurahmonov Adxamjon Sultonboyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article reveals the domestic potential of food production. A set of measures to be implemented in the Fergana region to achieve the strategic indicators of agricultural development of the Republic of Uzbekistan for 2020-2030 has been developed. Scientific proposals and practical recommendations aimed at improving the regional food market are given.